Growth-Promoting Effects of Dark Septate Endophytes Fungus Acrocalymma on Tomato (Solanum lycopersicum) - Xiaoxiao Feng; Ying Jin; Zhupeiqi Zhong; Yongli Zheng; Huiming Wu (Journal of Fungi, 2025)
This study investigates the potential role of Acrocalymma dark septate endophytic (DSE) fungi in promoting the growth of Solanum lycopersicum (tomato). Recognized as important symbionts that enhance plant growth and resilience under stress, particularly Acrocalymma species, DSE fungi were the focus of this investigation. Specifically, four stains isolated from gramineous plant roots (Acrocalymma sp. E00677, Acrocalymma vagum E00690, Acrocalymma chuxiongense E01299A, and Acrocalymma chuxiongense E01299B) were examined. Morphological characteristics were observed using three different media, confirming typical DSE traits such as dark pigmentation and septate hyphae. Phylogenetic analysis using six genetic markers (ITS, LSU, SSU, tef1, rpb2, and tub2) placed the strains within the Acrocalymma genus. Co-culture test and physiological index measurements showed that all strains significantly enhanced root development, as evidenced by an increased root-to-shoot ratio and a higher number of lateral roots. Additionally, the Acrocalymma DSE strains elevated chlorophyll a, chlorophyll b, and total chlorophyll content, suggesting improved photosynthetic efficiency. Anthocyanin levels were also increased in the tomato leaves, indicating enhanced antioxidative defense mechanisms. Among these strains, Acrocalymma vagum E00690 exhibited the most substantial effect on root activity. The widespread presence of 325 Acrocalymma isolates from 25 countries underscores its broad ecological adaptability. These findings suggest that Acrocalymma DSE fungi positively influence tomato growth, with potential implications for improving plant resilience under environmental stress. This study highlights the importance of further exploring DSEs, particularly Acrocalymma fungi, to better understand their ecological roles in agricultural practices, particularly in tomato cultivation.